2018
DOI: 10.2147/ijn.s164355
|View full text |Cite
|
Sign up to set email alerts
|

Global trends in nanomedicine research on triple negative breast cancer: a bibliometric analysis

Abstract: Nanotechnology has emerged as a promising tool in the clinic to combat several difficult-to-manage diseases, such as cancer, which is the second leading cause of death worldwide. Chemotherapeutic drugs present several limitations such as undesired side effects, low specificity, resistance, and high relapse rates. Triple negative breast cancer (TNBC) is caused by cells that lack specific receptors in their membrane, such as estrogen (ER+) and progesterone (PR+) receptors, or by cells that do not express the amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…Although a large number of databases are used for evaluation research at global level [45][46][47], the current study uses the Scopus database which is widely accepted among researchers for the purposes of high quality bibliometric analyses [44,[48][49][50][51][52][53]. Scopus is the world's largest abstract and citation database of peer-reviewed research literature, and is an established resource for identifying biomedical research including MEDLINE documents, and includes a higher level of detail than PubMed including the country of origin and citations per document [47,54].…”
Section: Methodsmentioning
confidence: 99%
“…Although a large number of databases are used for evaluation research at global level [45][46][47], the current study uses the Scopus database which is widely accepted among researchers for the purposes of high quality bibliometric analyses [44,[48][49][50][51][52][53]. Scopus is the world's largest abstract and citation database of peer-reviewed research literature, and is an established resource for identifying biomedical research including MEDLINE documents, and includes a higher level of detail than PubMed including the country of origin and citations per document [47,54].…”
Section: Methodsmentioning
confidence: 99%
“…There are few scholarly investigations concerning the publishing trends related to the medical applications of nanotechnologies and nanosciences. Teles and collaborators [17] have focused on the potential promises of nanomedicine for the management and treatment of triple negative breast cancer (TNBC), mining the literature (Scopus database) from 2012 to 2017. Authors found that most articles concerned antineoplastic agents tested using in-vitro models, cell cultures, or animal models.…”
Section: Discussionmentioning
confidence: 99%
“…The Scopus database was selected to perform a literature search, once it is considered to be a reliable process for acquiring bibliometric indicators, such as abstracts, citations, and other data mostly used in bibliometric studies in the area of medicine [44,45]. Two investigators (JMA and RHGT) independently conducted a search in the Scopus database using the following keywords and Boolean operators: (microRNA OR miRNA OR miRNAs OR miR-1 OR miR-2 OR miR-3 OR miR-4 OR miR-5 OR miR-6 OR miR-7 OR miR-8 OR miR-9) and (obesity AND "adipose tissue" ORadipogenesis.…”
Section: Methodsmentioning
confidence: 99%